2021
DOI: 10.1016/j.tranon.2021.101187
|View full text |Cite
|
Sign up to set email alerts
|

Effects of locoregional radiotherapy in de novo metastatic nasopharyngeal carcinoma: A real-world study

Abstract: Highlights Locoregional radiotherapy can prolong OS for patients with de novo metastatic nasopharyngeal carcinoma. Nasopharyngeal carcinoma patients with oligometastic disease can benefit from locoregional radiotherapy rather than polymetastatic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 38 publications
0
12
1
Order By: Relevance
“…Unlike previous studies, our model combined both anatomical and biological factors, and the optimal factors were selected to risk stratify patients accurately [ 16 , 17 ]. Based on our model, dmNPC patients were divided into three risk categories with significant differences in OS: the low-risk group (involved lesions ≤ 4 without liver involvement), the intermediate-risk group (involved lesions ≤ 4 with liver involvement or involved lesions > 4 with EBV-DNA < 62,000 copies/ml) and the high-risk group (involved lesions > 4 with EBV-DNA > 62,000 copies/ml).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous studies, our model combined both anatomical and biological factors, and the optimal factors were selected to risk stratify patients accurately [ 16 , 17 ]. Based on our model, dmNPC patients were divided into three risk categories with significant differences in OS: the low-risk group (involved lesions ≤ 4 without liver involvement), the intermediate-risk group (involved lesions ≤ 4 with liver involvement or involved lesions > 4 with EBV-DNA < 62,000 copies/ml) and the high-risk group (involved lesions > 4 with EBV-DNA > 62,000 copies/ml).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two retrospective studies from our center and other center found that the OMD model with ≤2 organs and ≤5 metastatic lesions could not only effectively evaluate the prognosis of patients with M1-NPC, but could also help to screen populations benefit from LR-RT. 4,13 Therefore, we believe that OMD (≤2 metastatic organs and ≤5 lesions) may be an appropriate definition in M1-NPC.…”
Section: Discussionmentioning
confidence: 99%
“…De novo metastatic nasopharyngeal carcinoma (M1‐NPC) accounts for 5%–10% of newly diagnosed NPC cases 1 . M1‐NPC generally has a poor long‐term survival, with 3‐year overall survival (OS) of 20%–30% 2–4 . However, heterogeneity exist.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations